The Influence of Different Terrains on the Wind Pressure Distribution of Glass Curtain Wall in Airport Terminals in Mountainous Areas - Cheng Pei; Xiaomin Zhang; Xiaokang Cheng; Xiongwei Yang; Cunming Ma (Advances in Civil Engineering)
Aiming the issue of wind pressure distribution characteristics of airport terminal glass curtain walls in mountainous areas, wind tunnel tests have been conducted to investigate glass curtain walls in airport terminals under different terrains (at mountain heights of 0, 30, 60, 90 m [H1, H2, H3, H4] and under surrounding high mountains of 80, 130, 150 m [H5, H6, H7]). Based on experimental data, a comparative analysis was conducted on the effects of different terrains on the mean and pulsating wind pressures, non-Gaussian characteristics, peak factor, and extreme wind pressure. The results show that the larger values of the mean and pulsating wind pressures under different terrains appear at the corners of the curtain wall edges. Furthermore, the skewness, kurtosis, and wind pressure probability density function values at the corners of the curtain wall edges significantly deviate from the standard Gaussian distribution, exhibiting significant non-Gaussian characteristics. The majority values of peak factors range from 3.5 to 5.0, far higher than the recommended value of 2.5 in Chinese specification and code (GB 50009-2012). Moreover, the values of extreme wind pressure under terrains H1, H2, H3, and H4 were greater than that under terrains H5, H6, and H7. At mountain heights H1, H2, H3, and H4, the increasing mountaintop height has a certain increasing effect on the extreme wind pressure. The maximum increase of 96.5% and 82.8% in mountain height H3 and H4 compared to H1. However, the increase in the height of surrounding mountains has a reducing effect on the extreme wind pressure. Research can provide useful suggestions and references for the design, construction, and site selection of terminals in similar airports.